2000
DOI: 10.1152/ajpheart.2000.278.1.h74
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine is not responsible for local metabolic control of coronary blood flow in dogs during exercise

Abstract: The purpose of this investigation was to quantitatively evaluate the role of adenosine in coronary exercise hyperemia. Dogs (n = 10) were chronically instrumented with catheters in the aorta and coronary sinus, and a flow probe on the circumflex coronary artery. Cardiac interstitial adenosine concentration was estimated from arterial and coronary venous plasma concentrations using a previously tested mathematical model. Coronary blood flow, myocardial oxygen consumption, heart rate, and aortic pressure were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 33 publications
10
87
1
3
Order By: Relevance
“…Glibenclamide treatment significantly decreased the slope of this relationship (P ϭ 0.03), indicating that K ATP channels are important to functional exercise coronary hyperemia in alloxaninduced diabetes. Because of the normally high oxygen extraction by the left ventricle (8,22,24), the data points and regression lines lie extremely close to the line of 100% oxygen extraction (oxygen consumed ϭ oxygen delivery) illustrated in Fig. 2.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Glibenclamide treatment significantly decreased the slope of this relationship (P ϭ 0.03), indicating that K ATP channels are important to functional exercise coronary hyperemia in alloxaninduced diabetes. Because of the normally high oxygen extraction by the left ventricle (8,22,24), the data points and regression lines lie extremely close to the line of 100% oxygen extraction (oxygen consumed ϭ oxygen delivery) illustrated in Fig. 2.…”
Section: Resultssupporting
confidence: 62%
“…A more sensitive index of the relationship between coronary blood flow and myocardial metabolism is shown in the plot of coronary venous PO 2 versus MVO 2 (Fig. 4) (4,5,8,20,22,24). K ATP channel blockade with glibenclamide made the slope of this relationship more negative (P ϭ 0.01), indicating that K ATP channels contribute to local metabolic coronary vasodilation in experimental diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We [20,44] and others [10,11,45] previously demonstrated that adenosine also plays a physiological role in regulating coronary resting flow in human [11], swine [10], dogs [45], guinea pigs [46], and mice [20,44], while some other groups failed to observe an endogenous role of adenosine [3,47,48], which leaves this scientific topic controversial. This discrepancy may be due to different animal models, differences in species, and/or different agonists and antagonists applied in these studies [19].…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Pmentioning
confidence: 99%